Serum visfatin in patients with type two diabetic retinopathy - I. N. Salman; N. U. G. Mohammed; S. E. Atta; B. A. Abed; R. Salim (Сахарный диабет)
BACKGROUND: The primary cause of blindness in diabetics is diabetic retinopathy (DR), the most common microvascular complication of diabetes, and visual impairment. Visfatin is an adipocytokine that aids in insulin activity during gestational diabetes and pregnancy.AIM: This study aimed to estimate serum visfatin levels in DR, proliferative (PDR), non-proliferative (NPDR), and healthy subjects (HS).MATERIALS AND METHODS: A 120-patient case-control study with a history of T2DM for more than 5 years as well as 30 healthy subjects enrolled in the study. Patients group divided into three sub-groups, DM, PDR, and NPDR. Visfatin levels were measured using a commercially available enzyme-linked immunosorbent assay kit. Triglyceride (TG), serum cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) levels and glycated haemoglobin (HbA1c) were assessed.RESULTS: The PDR patients and patients with poor glycemic control showed significantly increased visfatin levels compared with the HS group and T2DM patients without DR. The TC, TG, and DR group’s LDL-C levels were noticeably higher and significantly greater in PDR than in the group of HS.CONCLUSION: Visfatin levels have been linked to both the severity and existence of DR. and more in patients with poor glycemic control. Elevated lipids were associated with DR risk.